Implementación del sistema de gestión de la seguridad y salud en el trabajo, de acuerdo con los lineamientos establecidos por el decreto 1072 del 2015, resolución 1111 del 2017, ley 1562 del 2012 y decreto 052 del 2017 para la compañía Invotecsa SAS (2019)
The objective of this degree project is to implement the Occupational Health and Safety Management System based on the guidelines established in Decree 1072 of 2015 and Resolution 1111 of 2017 in the company Invotecsa Innovaciones Tecnológicas SAS, located in the Bogotá City in the neighbourhood of Teusaquillo, which has as its main activity "Computer consulting activities and facilities management activities", among others. This in order to minimize the hazards and risks associated with each of the activities that workers are exposed to on a daily basis and in this way to achieve an adequate work environment and likewise can perform their functions in optimal, safe, reliable conditions, in addition to comply fully with the requirements demanded by current legal regulations.